PENILIAN KINERJA TENAGA SURVAILANS KESEHATAN (GASURKES) DEMAM BERDARAH DENGUE (DBD) DI KECAMATAN TEMBALANGKOTA SEMARANG - Mirsa Octavia Wardayani; Nina Widowati (Journal of Public Policy and Management Review, 2017)
Dengue Hemorrhagic Fever is the one of the most endemic disease in Indonesia. One of the biggest city in Indonesia, Semarang, turn out to be the one of the most dengue fever patient every years.. In Peraturan Walikota Kota Semarang No. 27B Tahun 2012 tentang Petunjuk Pelaksanaan Peraturan Daerah No. 5 Tahun 2010, it explained that control of Dengue Hemorrhagic Fever involving society, Local Government and Public Health Office which is represented with Health Surveillance Dengue Hemorrhagic Fever Officer. Tembalang district is the one of the most dengue fever cases on Semarang Disctrict on 2014 and 2015. The existence of Health Surveillance Dengue Hemorrhagic Fever Officer in Tembalang District didn’t completely control the disease of dengue fever on that district. The result of the research will show that work performance of Health Surveillance Dengue Hemorrhagic Fever Officer on Tembalang District need to improved to be better. One of the aspect need to be improved is work quality aspect, work quantity and using time at work. From this research, there are reccomendation to add training for Health Surveillance Dengue Hemorrhagic Fever Officer. Training needed to improve work quality of Health Surveillance Dengue Hemorrhagic Fever Officer, determine quantity needed of Health Surveillance Dengue Hemorrhagic Fever Officer in each region so that it would improve work quantity of Health Surveillance Dengue Hemorrhagic Fever Officer. Furthermore, there was a need to apply presence system and monthly report to minimalyze mistake, and improving cooperation with various parties